The flight of the condor a wildlife exploration of the Andes - Andrews, Michael, 1940- (London : British Broadcasting Corporation, 1992)
The programme is about the remarkably varied animal population of the Andes, the world's longest and most spectacular mountain chain
An adaptation of a television series
Copy available in DVD format
Photographers, Hugh Miles ... [et.al.] ; narrator, Andrew Sachs ; film editor, Pete Heeley, Teresa Hughes ; music, Inti Ilimani, Gumary
Keywords: Natural history -- Andes Region